2009 IEEE International Symposium on Industrial Electronics 2009
DOI: 10.1109/isie.2009.5217935
|View full text |Cite
|
Sign up to set email alerts
|

Towards a dynamic emotional model

Abstract: Emotions in general are a complex phenomenon to comprehend. They have been known to influence decisions as also behavior. Several computational models for emotions have been attempted. In this paper we present the dynamics and working of a multi-agent emotion generating system. Three basic emotions viz. happiness, fear and anger have been used to generate a resultant internal mood for a machine or a robot whose state depends on the immediate past. We compare the results obtained with those generated by a conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…We considered the first human as the experiment subject and the second human as the control subject. Based on the human-human study, we found the following major task situations/contexts/events and the corresponding affects, as given in Table 2 [45][46][47][48]. Table 2 shows the major events that occurred during the human-human collaboration and the ways the humans, especially the first humans, expressed the situations/events through affective expressions.…”
Section: Inspiration From a Human-human Collaborative Task: The Biomi...mentioning
confidence: 99%
See 1 more Smart Citation
“…We considered the first human as the experiment subject and the second human as the control subject. Based on the human-human study, we found the following major task situations/contexts/events and the corresponding affects, as given in Table 2 [45][46][47][48]. Table 2 shows the major events that occurred during the human-human collaboration and the ways the humans, especially the first humans, expressed the situations/events through affective expressions.…”
Section: Inspiration From a Human-human Collaborative Task: The Biomi...mentioning
confidence: 99%
“…We called this test the affect recognition test. To implement the HRC of Figure 3, we just replaced the first human of Figure 4 with a robot, selected a slightly more representative task instead of the simple task of Figure 4, and enabled the robot to express various affective expressions similar to that the first human did at different events [45][46][47][48].…”
Section: Inspiration From a Human-human Collaborative Task: The Biomi...mentioning
confidence: 99%
“…In addition to challenges in comparison between publications, it is often not possible to compare each system to anything outside of the proposed control from within the study. In our review we found only one paper that compared their emotional model with a baseline system [61], every other publication compared only one emotional model usually to a control group which had no emotion added.…”
Section: A Paradigm Features 1) Distinct Approaches For Interaction A...mentioning
confidence: 99%
“…What is used are terms like 'emotion' or 'feeling' without the proper knowledge of the scientific field defining those terms (see eg. [8] or [9]). The terms are taken from theoretical work, often mixed together from different theories and used without proper check for interoperability.…”
Section: B Interdisciplinary Approachmentioning
confidence: 99%